REDUCING THE VISCOSITY OF OIL-WATER EMULSIONS USING HYDROCARBON SOLVENTS - Ochilov , Abduraxim; Uzakbaev, Kamal (Techscience uz - Topical Issues of Technical Sciences, 2024)
Today, technologies for dehydration and desalting of stable water-oil emulsions do not meet modern requirements of the oil and gas industry. In the process of destruction of stable water-oil emulsions, losses of valuable oil with wastewater, high consumption of expensive imported demulsifiers, etc. are observed. To reduce the amount of demulsifiers, it is necessary to choose hydrocarbon solvents as viscosity reducers for highviscosity heavy oil emulsions.